Contribuição ao estudo da morfologia craniana das espécies brasileiras dos gêneros Acanthochelys e Platemys (Chelonia: Chelidae) - Guedes, Marcia Denise (1992)
The genus Acanthochelys is composed by four species, but only A. macrocephala had its cranial characters described. On the other hand, the genus Platemys involves only one species, P. platycephala, which had these characters described. Both genera were treated as synonyms until recently, when it was suggested their distinction, based on chromosomial characters. This distinction was accepted without any comments or characterization of the genera, and subsequently they were confirmed, after biochemical studies. This work shows cranial characters of species of both genera, as a contribution for the osteological characterization of these taxons. The results agree with both chromosomial and biochemical data and show the great interespecific variation in the skull morphology among the species of Acanthochelys.